2013
DOI: 10.1097/01.olq.0000431358.18959.d4
|View full text |Cite
|
Sign up to set email alerts
|

The Legal Aspects of Expedited Partner Therapy Practice

Abstract: Background Expedited partner therapy (EPT) is a potential partner treatment strategy. Significant efforts have been devoted to policies intended to facilitate its practice. However, few studies have attempted to evaluate these policies. Methods We used data on interviewed gonorrhea cases from 12 sites in the STD Surveillance Network (SSuN) in 2010 (n=3,404). Patients reported whether they had received EPT. We coded state laws relevant to EPT for gonorrhea using Westlaw legal research database, and the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…For example, a multi-state study of the relationship between state-level EPT policies (e.g., laws and medical/pharmacy board statements) and gonorrhea patients receiving EPT found evidence that EPT use is higher in states with policies that are supportive to its use. [17] Additionally, an assessment of federally qualified health centers in New York City conducted in 2012 found that approximately half of governing organizations had written policies permitting EPT. [18] Of clinical sites examined, 80% provided EPT with slightly more use (86%) at sites whose governing organization had a written EPT policy.…”
Section: Policies Focused On Std Prevention Issuesmentioning
confidence: 99%
“…For example, a multi-state study of the relationship between state-level EPT policies (e.g., laws and medical/pharmacy board statements) and gonorrhea patients receiving EPT found evidence that EPT use is higher in states with policies that are supportive to its use. [17] Additionally, an assessment of federally qualified health centers in New York City conducted in 2012 found that approximately half of governing organizations had written policies permitting EPT. [18] Of clinical sites examined, 80% provided EPT with slightly more use (86%) at sites whose governing organization had a written EPT policy.…”
Section: Policies Focused On Std Prevention Issuesmentioning
confidence: 99%
“…Expedited partner therapy legal status 11 and its dynamic nature is caused by advocacy efforts to increase permissibility. 20,21 The Centers for Disease and Control Prevention presents each state's EPT legal status and offers a legal/policy toolkit at www.cdc.gov/std/ept/legal.…”
mentioning
confidence: 99%
“…So the legal barrier continues to deteriorate and it appears that legalizing EPT in all states is a winnable battle. A recent study by Cramer et al 9 found that if EPT was legal, providers were almost 2.5 times more likely to offer it, yet only 9.5% of interviewed patients with gonorrhea reported receiving EPT for their partners. EPT legality is, therefore, a necessary but not sufficient criterion for uptake.…”
Section: Legalizationmentioning
confidence: 99%
“…4 Where policies by professional organizations supporting EPT exist, providers are more likely to use it. 9 Favorable policies, professional endorsement, legal status and funding are needed to persuade many providers to offer EPT.…”
Section: Providers Offermentioning
confidence: 99%